The chromatographic assay of 4‐hydroxynonenal as a biomarker of diseases by means of MEPS and HPLC technique. (9th September 2014) - Ligor, Magdalena; Ligor, Tomasz; Gadzała‐Kopciuch, Renata; Buszewski, Bogusław
Abstract: The aim of this study was to develop and validate a new analytical method for the determination of 4‐hydroxy‐2‐nonenal (4‐HNE) in biological samples while applying microextraction by packed sorbent as a sample preparation method and HPLC with UV–vis detection. Various microextraction by packed sorbent (MEPS) sorbents like C2, C8, C18, M1 (80% C8 and 20% SCX) and silica were used to separate 4‐HNE from biological samples. The highest affinity of 4‐HNE was observed for sorbents like C18 . The extraction efficiency was in the range from 47.4 to 89.2% dependent on the concentration of 4‐HNE. Lower efficiency of 4‐HNE extraction was obtained with use of MEPS packings such as C8 and M1. The extraction efficiency was in the range from 35.2 to 66.3% for packing C8 and from 34.2 to 64.3% for packing M1, respectively. The limit of detection and lower limit of quantitation for UV–vis detection were respectively 4.5 and 9.0 nmol/mL. The proposed method can be used for the evaluation of extraction efficiency of 4‐HNE in biological sample because the values of lower limit of quantitation are lower than the determined amounts of the analyte in samples. The method yields excellent performance of quantification and identification in analysis of inflammation biomarkers. Copyright © 2014 John Wiley & Sons, Ltd.